2014
DOI: 10.1016/j.chemosphere.2013.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of exposure to brominated flame retardants: A systematic review

Abstract: Although there is suggestive evidence that exposure to BFRs is harmful to health, further epidemiological investigations particularly among children, and long-term monitoring and surveillance of chemical impacts on humans are required to confirm these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 77 publications
1
107
0
1
Order By: Relevance
“…Humans are primarily exposed through inhalation of dust, dermal absorption and intake of fish, poultry, meat and dairy products. PBDEs are toxic and studies in animals and epidemiological or HBM studies in humans have shown neurotoxic, endocrine disrupting and carcinogenic effects (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Humans are primarily exposed through inhalation of dust, dermal absorption and intake of fish, poultry, meat and dairy products. PBDEs are toxic and studies in animals and epidemiological or HBM studies in humans have shown neurotoxic, endocrine disrupting and carcinogenic effects (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, an increasing number of longitudinal prospective cohort studies were undertaken to address this knowledge gap on the association between EDC exposure and child health outcomes; including studies into asthma, neurobehavioral problems, thyroid dysfunction and obesity (17)(18)(19)(20). Given that epidemiologic studies depend upon appropriate and accurate measurement of EDC exposure, there has been increasing discussion regarding the design and use of various exposure assessment methods for these studies, particularly those that are appropriate for use in children (21,22).…”
Section: Pyrethroids and Organophosphatesmentioning
confidence: 99%
“…The main source of flame retardants in humans is air (inhalation), dust, water, food, and for some person's exposure to the chemicals. More dangerous is exposure to FRs by young children who are less able to detoxification and elimination of environmental pollution from their organisms, which can lead to diseases in adulthood (Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their exposure to a particular group of compounds many negative effects were observed such as thyroid dysfunction, changes in homeostasis, neurotoxicity, neurobehavioral and reproduction changes (including delayed puberty, reduced pregnancy, changes in menstruation), cancer (including breast cancer) and many others (Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%